The mechanisms of action underlying the efficacy of psychological nightmare treatments: A systematic review and thematic analysis of discussed hypotheses. (June 2018) - Rousseau, Andréanne; Belleville, Geneviève
Summary: Studies of psychotherapeutic treatments for nightmares have yielded support for their effectiveness. However, no consensus exists to explain how they work. This study combines a systematic review with a qualitative thematic analysis to identify and categorize the existing proposed mechanisms of action (MAs) of nightmare treatments. The systematic review allowed for a great number of scholarly publications on supported psychological treatments for nightmares to be identified. Characteristics of the study and citations regarding potential MAs were extracted using a standardized coding grid. Then, thematic analysis allowed citations to be grouped under six different categories of possible MAs according to their similarities and differences. Results reveal that an increased sense of mastery was the most often cited hypothesis to explain the efficacy of nightmare psychotherapies. Other mechanisms included emotional processing leading to modification of the fear structure, modification of beliefs, restoration of sleep functions, decreased arousal, and prevention of avoidance. An illustration of the different variables involved in the treatment of nightmares is proposed. Different avenues for operationalization of these MAs are put forth to enable future research on nightmare treatments to measure and link them to efficacy measures, and test the implications of the illustration.